Age- and sex-specific reference values for the Banff Patella Instability Instrument (BPII 2.0) in the German population based on 1309 participants - Zimmermann, Felix; Balcarek, Peter; Giesinger, Johannes Maria; Pilz, Micha Johannes; Liebensteiner, Michael; Dirisamer, Florian; Becher, Christoph (Knee surgery, sports traumatology, arthroscopy, 2025)
Purpose The Banff Patella Instability Instrument (BPII 2.0) is a validated patient-reported outcome measure to assess disease-specific quality of life in individuals with lateral patellar instability. This study aimed to establish age- and sex-specific reference values for the German general population and to identify participant-specific factors influencing BPII 2.0 scores. Methods Data were collected using quota sampling from 1309 participants via an online panel. The sample was stratified into 12 subgroups (n ≥ 100 per subgroup) based on age and sex and weighted to align with German census data. Demographic and health-related data were collected; descriptive statistics and percentiles were used to report age- and sex specific reference values. An analysis of variance (ANOVA) model was built to examine the influence of body mass index (BMI) and comorbidities on BPII 2.0 scores. Results Males showed higher BPII 2.0 scores compared to females (75.1 ± 24.0 points vs. 71.0 ± 26.8 points; p < 0.01). Participants aged 14-30 years showed significantly higher mean scores (79.6 ± 20.5 points) than those participants >30 years (71.2 ± 26.4 points) (p < 0.01). ANOVA displayed significant (p < 0.001) decreasing mean scores with an increase in BMI categories (76.0 points; CI 73.9-78.0 points in under/normal weight compared to 64.3 points; CI 60.2-68.3 points in participants with obesity II + III). Participants with self-reported comorbidities showed significantly (p < 0.001) lower mean scores (60.0 points; CI 57.9-62.1 points) compared to persons without comorbidities (82.9 points; CI 80.6-85.2 points). The regression analysis further showed decreasing BPII 2.0 scores with increasing age (−0.24 points per life year). Conclusion This study provides the first age- and sex-stratified reference BPII 2.0 values for the German population. Higher age, female sex, the presence of comorbidities and a higher BMI have a significant negative impact on reference values for the BPII 2.0. Level of Evidence Level IV.
Zuerst veröffentlicht: 28. Oktober 2025
Gesehen am 09.12.2025